2017
DOI: 10.1016/j.chroma.2017.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Thin-layer chromatography coupled with high performance liquid chromatography for determining tetrabromobisphenol A/S and their derivatives in soils

Abstract: As brominated flame retardants (BFRs), tetrabromobisphenol A/S (TBBPA/S) and their derivatives have raised wide concerns owing to their widely usage, distributions and adverse effects on human health, thus monitoring these BFRs was urgently needed. In this study, a rapid and cost-effective method based on thin-layer chromatography (TLC) sample pre-treatment coupled with high performance liquid chromatography-diode array detector (HPLC-DAD) (UV=214nm) was developed for determining TBBPA/S and their derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Correspondingly, matrix-matched standard solutions were prepared (50, 500 ng/mL) by mixing the corresponding standards with concentrated sample extracts. The matrix-induced signal suppression or enhancement was determined by comparison with the signals of pure standards [22]. The LODs and LOQs were established based on the lowest concentration with a signal-to-noise ratio (S/N) of 3:1 and 10:1.…”
Section: Methods Validationmentioning
confidence: 99%
“…Correspondingly, matrix-matched standard solutions were prepared (50, 500 ng/mL) by mixing the corresponding standards with concentrated sample extracts. The matrix-induced signal suppression or enhancement was determined by comparison with the signals of pure standards [22]. The LODs and LOQs were established based on the lowest concentration with a signal-to-noise ratio (S/N) of 3:1 and 10:1.…”
Section: Methods Validationmentioning
confidence: 99%
“…Studies have also indicated that an etherified group at a position in the phenolic rings of TBBPA is crucial for the chemically induced adipogenic effects . Furthermore, several analogues of TBBPA, such as tetrabromobisphenol S bis­(2,3-dibromopropyl ether) and TBBPA bis­(2,3-dibromopropyl ether), have been introduced into markets. , These analogues may be released into the environment during the lifetime of products, and thus may widely occur in the environment and biota together with their transformation products. , …”
Section: Introductionmentioning
confidence: 99%
“…TBBPA, TBBPS and TCBPA known as common brominated flame retardants, they are also often used in plastic paints, synthetic textiles, and electrical devices. 22,23 most hazardous and anti-estrogen chemicals, consisting of PCB77 and other 11 congeners. 24 Moreover, non-dioxin-like PCBs like PCB28, PCB101, and PCB180 are also frequently reported.…”
Section: Table 1 Common Edcs With Their Toxicities and Adverse Effectsmentioning
confidence: 99%
“…TBBPA, TBBPS and TCBPA are known as common brominated flame retardants, and they are also often used in plastic paints, synthetic textiles, and electrical devices. 22,23…”
Section: Bisphenolsmentioning
confidence: 99%